Stanniocalcin 2 expression is associated with a favourable outcome in male breast cancer. (23rd August 2018) - Coulson‐Gilmer, Camilla; Humphries, Matthew P; Sundara Rajan, Sreekumar; Droop, Alastair; Jackson, Sharon; Condon, Alexandra; Cserni, Gabor; Jordan, Lee B; Jones, Louise J; Kanthan, Rani; Di Benedetto, Anna; Mottolese, Marcella; et al.
Abstract: Breast cancer can occur in either gender; however, it is rare in men, accounting for <1% of diagnosed cases. In a previous transcriptomic screen of male breast cancer (MBC) and female breast cancer (FBC) occurrences, we observed that Stanniocalcin 2 ( STC2 ) was overexpressed in the former. The aim of this study was to confirm the expression of STC2 in MBC and to investigate whether this had an impact on patient prognosis. Following an earlier transcriptomic screen, STC2 gene expression was confirmed by RT‐qPCR in matched MBC and FBC samples as well as in tumour‐associated fibroblasts derived from each gender. Subsequently, STC2 protein expression was examined immunohistochemically in tissue microarrays containing 477 MBC cases. Cumulative survival probabilities were calculated using the Kaplan–Meier method and multivariate survival analysis was performed using the Cox hazard model. Gender‐specific STC2 gene expression showed a 5.6‐fold upregulation of STC2 transcripts in MBC, also supported by data deposited in Oncomine™. STC2 protein expression was a positive prognostic factor for disease‐free survival (DFS; Log‐rank; total p = 0.035, HR = 0.49; tumour cells p = 0.017, HR = 0.44; stroma p = 0.030, HR = 0.48) but had no significant impact on overall survival (Log‐rank; total p = 0.23, HR = 0.71; tumour cells p = 0.069, HR = 0.59; stroma p = 0.650, HR = 0.87). Importantly, multivariate analysis adjusted for patient age at diagnosis, node staging, tumour size, ER, and PR status revealed that total STC2 expression as well as expression in tumour cells was an independent prognostic factor for DFS (Cox regression; p = 0.018, HR = 0.983; p = 0.015, HR = 0.984, respectively). In conclusion, STC2 expression is abundant in MBC where it is an independent prognostic factor for DFS.